Off-Road vehicle suspension performance improvement using linear quadratic regulator techniques - Bello, Musa Mohammed; Shafie, Amir Akramin; Khan, Md. Raisuddin (2015)
The main purpose of vehicle suspension system is to isolate the vehicle main body from any road geometrical irregularity in order to improve the passengers ride comfort and to maintain good handling stability. The present work aim at designing a control system for an active suspension system which is widely applied in today’s automotive industries. The design implementation involves construction of a state space model for half vehicle with four degree of freedom and a development of full state-feedback controller using Linear Quadratic Regulator (LQR) techniques. The performance of active suspension system was assessed by comparing its response to that of passive suspension system. Simulation using Matlab/Simulink environment shows that, even at resonant frequency the active suspension system develops a good dynamic response and a better ride comfort when compared with the passive suspension system.